2011
DOI: 10.1007/s00520-011-1271-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical exercise interventions in prostate cancer patients—a systematic review of randomized controlled trials

Abstract: Current data suggest that incontinence, fitness, fatigue, body constitution, and also quality of life can be improved by clinical exercise in patients during and after prostate cancer. Studies were mostly ranked evidence level "2b." Only four studies, all conducted during medical treatment, reached the level "1b." It seems to be that "supervised exercise" is more effective than "non-supervised exercise." For future research, further randomized controlled trials with high methodological quality need to be condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
157
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(171 citation statements)
references
References 59 publications
4
157
0
10
Order By: Relevance
“…Fourteen systematic reviews found an improvement in qol for patients with cancer participating in an exercise intervention during the active treatment or post-treatment period 11,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 .…”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen systematic reviews found an improvement in qol for patients with cancer participating in an exercise intervention during the active treatment or post-treatment period 11,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…All systematic reviews found positive changes in both muscular and aerobic fitness 11,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]55,56 . Of the sixteen rcts that measured muscular or aerobic fitness, or both 10,14,29,30,34,35,37,39,40,[44][45][46][47][48]52,54 , eleven found significant positive changes in the exercise groups 10,14,29,30,34,35,37,39,[44][45][46]48 .…”
Section: Muscular and Aerobic Fitnessmentioning
confidence: 99%
See 1 more Smart Citation
“…A targeted physical exercise program can, for example, positively influence the side effects of a prostate cancer treatment. A significant reduction of incontinence following a controlled exercise intervention has been demonstrated in several randomized studies [6,59].…”
mentioning
confidence: 92%
“…Modification of lifestyle factors has been shown to play a role in reducing the risk of developing colorectal cancer, including modifications in excess weight, poor diet, smoking, alcohol excess and physical inactivity [1][2][3][4][5][6]. However, given the difficulty in performing randomised controlled trials in lifestyle interventions in colorectal cancer, there is doubt about the feasibility of such interventions [7,8]. With this in mind, we have recently published a systematic review [9] which sought to collate the evidence for the feasibility of performing lifestyle factor interventions in patients with colorectal cancer, allowing conclusions on the short and long-term health benefits to be drawn.…”
mentioning
confidence: 99%